Value of Contrast-Enhanced Ultrasound in the Ultrasound Classification of Cervical Tuberculous Lymphadenitis - Zhang, Ying; Yu, Tianzhuo; Su, Dongming; Tang, Wei; Yang, Gaoyi (Frontiers in Medicine, 2022)
Purpose: The purpose of this study was to investigate the clinical value of contrast-enhanced ultrasound (CEUS) in the classification and diagnosis of cervical tuberculous lymphadenitis (CTL). Materials and Methods: This retrospective analysis included 70 patients diagnosed with CTL via pathological examination or laboratory tests. All of the patients underwent both conventional ultrasound and CEUS. The conventional ultrasound and CEUS were compared to determine their level of agreement with pathological results of CTL. Results: Through conventional ultrasound, 18 (18/70, 25.7%), 25 (25/70, 35.7%) , 21 (21/70, 30.0%) and 6 (6/70, 8.6%) patients were classified as types I, II, III and Ⅳ CTL; however, through CEUS, 9 (9/70, 12.9%), 33 (33/70, 47.1%), 22 (22/70, 31.4%) and 6 (6/70, 8.6%) patients were categorized as types I, II, III and Ⅳ CTL, respectively. Classification results of conventional ultrasound showed substantial agreement (Kappa=0.693) with pathological results, with a coincidence rate of 78.6% (55/70); the coincidence rates of type II and type III were 71.0% (22/31) and 82.6% (19/23), respectively. The CEUS classification results showed nearly perfect agreement (Kappa=0.871) with the pathological results, with a coincidence rate of 91.4% (64/70); the coincidence rates of type II and type III were 93.6% (29/31) and 87.0% (20/23), respectively. Conclusion: Combined with conventional ultrasound, CEUS can provide further information on blood flow enhancement patterns, and identify the area of lymph node necrosis in CTL. This can contribute to more accurate ultrasound classification of CTL.